EFEKTIFITAS HAND TAPPING TERHADAP PEMENUHAN KEBUTUHAN PSIKOLOGIS (STRES DAN CEMAS) PADA DISMENORE, WANITA HAMIL, DAN MASA KLIMAKTERIUM : LITERATURE REVIEW - Dini Aulia Ramadhanty (2020)
Stress and anxiety can occur in women during their lifetime, including during menstruation, pregnancy, and the transition to menopause. These psychological problems can affect a woman's mental and physical health. Psychological problems can be overcome with non-pharmacological therapy, one of them is Hand Tapping, the pat technique can open up blocked energy which can help create a positive environment for well-being and will feel more energetic so that it can overcome the problem of stress and anxiety. The method used is Literature Review. Literature search uses Google Scholar, WorldCat, Science Direct, PubMed, and Semantic Scholar. The search results obtained as many as 298 articles and after going through the selection process obtained 10 articles. Inclusion criteria used were dysmenorrhea populations, pregnant women, and climacteric periods, interventions, namely hand tapping, outcomes, namely stress reduction and / or anxiety, articles in the range of 2016 - 2020, quasi experiment research designs, and the language used was language Indonesian and English. The number of articles reviewed was 10 articles. In the article, Hand Tapping interventions are applied and some are combined by comparing or combining Hand Tapping interventions with other interventions. The entire article yields that the Hand Tapping technique is effective in reducing stress and anxiety in dysmenorrhea, pregnant women and climacteric periods. In subsequent studies, researchers suggest that Hand Tapping interventions in dysmenorrhea, pregnant women, and climacteric periods experience stress and anxiety.